The Influence of C-Ions and X-rays on Human Umbilical Vein Endothelial Cells - Helm, Alexander; Lee, Ryonfa; Durante, Marco; Ritter, Sylvia (Frontiers in Oncology, 2016)
Damage to the endothelium of blood vessels, which may occur during radiotherapy, is discussed as a potential precursor to the development of cardiovascular disease. We thus chose human umbilical vein endothelial cells (HUVEC) as a model system to examine the effect of low and high linear energy transfer (LET) radiation. Cells were exposed to 250 kV X-rays or C-ions with the energies of either 9.8 MeV/u (LET=170 keV/µm) or 91 MeV/u (LET=28 keV/µm). Subculture of cells was performed regularly up to 49 days (~22 population doublings) post-irradiation. Immediately after exposure cells were seeded for the colony forming assay. Additionally, at regular intervals mitochondrial membrane potential (JC-1 staining) and cellular senescence (senescence associated β-galactosidase staining) were assessed. Cytogenetic damage was investigated by the micronucleus assay and the high-resolution mFISH technique. Analysis of radiation-induced damage shortly after exposure showed that C-ions are more effective than X-rays with respect to cell inactivation or the induction of cytogenetic damage (micronucleus assay) as observed in other cell systems. For 9.8 and 91 MeV/u C-ions relative biological effectiveness values of 2.4 and 1.5 were obtained for cell inactivation. At the subsequent time-points the number of micronucleated cells decreased to the control level. Analysis of chromosomal damage by mFISH technique revealed aberrations frequently involving chromosome 13 irrespective of dose or radiation quality. Disruption of the mitochondrial membrane potential was seen only a few days after exposure to X-rays or C-ions. Cellular senescence was not altered by radiation at any time-point investigated. Altogether our data indicate that C-ions were LET-dependently more effective in damaging endothelial cells shortly after exposure. Late damage to endothelial cells, however, was not found for the applied conditions and endpoints.